The Role of IoT-enabled Rehabilitation Centers in Supporting Drug Recovery Programs in Bali - Ismail, Ismail; Felecia, Felecia; Azizah, Anisa Kurniatul; Rahmawati, Diana (Westscience Press, 2025)
The integration of the Internet of Things (IoT) in healthcare has transformed rehabilitation practices, particularly in addressing substance abuse. This study explores the role of IoT-enabled rehabilitation centers in supporting drug recovery programs in Bali using a qualitative approach. Data were collected through semi-structured interviews with three informants: a healthcare professional, a technology expert, and a recovering individual. The findings reveal that IoT enhances drug recovery by enabling continuous monitoring, personalized treatment, and improved patient engagement. However, challenges such as infrastructure limitations, high costs, privacy concerns, and cultural resistance hinder widespread adoption. Strategies including collaborative funding, capacity-building initiatives, and robust policy development are recommended to overcome these obstacles. This study underscores the potential of IoT in transforming drug rehabilitation and highlights the need for targeted strategies to address implementation challenges in Bali.